2015
DOI: 10.1007/s13277-015-3987-9
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of miR-93 and miR-143 in human esophageal cancer

Abstract: Esophageal squamous cell carcinoma (ESCC) is the second and third most common malignancy in Iranian males and females, respectively. Treatment of ESCC is largely ineffective due to lack of detection at early stages of the disease. In recent years, miRNA, a small RNA molecule, has drawn much attention to researchers as a potential biomarker for esophageal cancer. miR-93 and miR-143 are two miRNA molecules reported to be frequently deregulated in various cancers, including prostate, stomach, cervix, and etc. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 63 publications
4
18
0
Order By: Relevance
“…In nasopharynx cancer, CCAT1 modulates paclitaxel sensitivity via the miR‐181a/CPEB2 axis . CCAT1 was also shown to act as an oncogene and promoted chemoresistance in docetaxel‐resistant lung adenocarcinoma cells . Furthermore, our results revealed that the expression of CCAT1 in ESCC cells is positively correlated with drug resistance, as we observed that higher CDDP sensitivity correlated with lower CCAT1 expression in several ESCC cell lines.…”
Section: Discussionsupporting
confidence: 62%
“…In nasopharynx cancer, CCAT1 modulates paclitaxel sensitivity via the miR‐181a/CPEB2 axis . CCAT1 was also shown to act as an oncogene and promoted chemoresistance in docetaxel‐resistant lung adenocarcinoma cells . Furthermore, our results revealed that the expression of CCAT1 in ESCC cells is positively correlated with drug resistance, as we observed that higher CDDP sensitivity correlated with lower CCAT1 expression in several ESCC cell lines.…”
Section: Discussionsupporting
confidence: 62%
“…MiR-93 acts as a tumor promoter and may also be used as a potential biomarker for esophageal squamous cell carcinoma (ESCC) [18, 19], which was in complete agreement with the current finding based on TCGA data.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, the expression of miR-93 was found to be significantly increased in esophageal squamous cell carcinoma (12). Moreover, miR-93 can promote the transforming growth factor (TGF)-β-induced epithelial-to-mesenchymal transition through directly targeting neural precursor cell expressed developmentally downregulated gene 4-like in lung cancer cells (13).…”
Section: Introductionmentioning
confidence: 99%